Análise do custo-benefício como procedimento de avaliação dos impactos das decisões públicas - Wedy, Ana Paula Martini Tremarin (2016)
The cost-benefit analysis is a decision procedure to improve the quality of government decision-making. The social problems never exist in isolation and any effort to solve a single problem will have a range of consequences, some of them likely unintended. CBA seeks rational regulation/legislation and to avoid unjustified economic burdens to society. In the USA, since 1981 agencies have to calculate the costs and benefits of their regulations and to proceed only if the benefits exceed or justify the costs. In Brazil that is no formal procedure to evaluate the impacts of public decisions. However, without a methodology for calculating the impacts, analysts are likely to rely on their own hunches and speculations and the results (from guesstimates) will fail in advances overall well-being relative to alternative decision procedures. But once recognised that CBA should lead the public decisions that are hard cases to handle: how to value life and health, how to deal with the interests of the future generations, how to deal with small risks and uncertainty in environmental questions, how to diverge from the conclusion recommended by CBA, how should the Courts contribute to the improvement of the procedure. The research attempt to explore those questions and how the government might saves money and lives with a tool that is designed to rationalize the public decisions that involve investments of the finite and scarce public resources.